Community Economic Empowerment Through Asset Based Commonity Devolopment Method (Study of the Role of Fatayat NU in Bawean Island, Gresik) - Ulfatun Najiha (Universitas Nahdlatul Ulama Sidoarjo, 2023)
Community economic empowerment is an effort to improve community welfare through increasing capacity and active participation in economic activities. One method that can be used to achieve community economic empowerment is asset-based community development (ABCD). The ABCD method takes a relational approach and utilizes the potential and resources that exist in the community. This approach focuses on identifying and empowering existing local resources, such as skills, knowledge, community networks and natural assets. Fatayat NU (Nahdlatul Ulama) as a women-based social organization has an important role in empowering the community economy at the grassroots. The role of Fatayat NU Bawean in empowering the community's economy through an asset-based community development (ABCD) approach. The first is to provide training in the form of Entrepreneur Workshop Activities. Assistance with halal certification for UMKM (Micro, Small, and Medium Enterprises) Products. Third, they provide access to local product marketing to increase awareness and visibilty. This research adopts a qualitative descriptive method, utilizing the Miles and Huberman field data analysis model. Primary data was collected through direct interviews with the NU Bawean Fatayat Branch (PC) administrators and the local community, while secondary data was gathered from magazines, articles and books.